Analisis Faktor-Faktor Kesulitan Belajar Mahasiswa pada Mata Kuliah Manajemen Keuangan di Program Studi Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Batanghari Jambi - Diliza Afrila; Mutia Samrotul Fuadah (Universitas Batanghari Jambi, 2020)
This study aims to determine (1) the description of student learning difficulties in the Financial Management course in the Economic Education Study Program of the Teaching and Education Faculty of Batanghari University, Jambi, and (2) the factors of student learning difficulties in the Financial Management course in the Educational Study Program Economics of Teacher Training and Education Faculty, Batanghari University, Jambi. This type of research is descriptive research with a quantitative approach. The study population was students of the Economic Education Study Program Semester IV and VI Academic Year 2018/2019, totaling 48 people. The sampling technique is saturated sampling, so that the entire population is made into a research sample. The results showed that (1) the learning difficulty variable was in the high category with an average of 4.32 and the Respondent's Achievement Level (TCR) of 86.43, and (2) There were 10 (ten) dominant factors affecting student learning difficulties, i.e. (a) Factor 1 which is given the Psychological Factor identity, which consists of statement items F3.2, F3.3, F4.1, F4.2, F5.2, F5.3, F5.4, and F5.5, (b) Factor 2 which is given the identity of the State of the Building, which consists of statement items F11.1 and F11.2, (c) Factor 3 which is assigned the identity of Peer Environment, consisting of statement items F14.1 and F14.2, ( d) Factor 4 which is given the identity of Physical Factor, which consists of statement items F1 and F2, (e) Factor 5 which is given the identity of Lecturer Competence, which consists of statement items F9.1, F9.3, F9.4, and F9. 5, (f) Factor 6 which is given Family Factor identity, which consists of statement items F6.2, F7.1, F7.2, F8.1 and F8.2, (g) Factor 7 which is given Identification of Able Discipline s, which consists of statement items F12, (h) Factor 8 which is given the Identity of Learning Resources, which consists of statement items F10.1, F10.2, F10.3, and F10.4, (i) Factor 9 which is given an identity Mass Media, which consists of statement items F13.1 and F13.2, and (j) Factor 10 which is given the Learning Habit identity, which consists of statement items F13.3.